(untitled) (Research, Society and Development, 2025)
In today’s highly competitive business environment, companies can no longer survive with a transactional attitude towards customers, and it is necessary to focus on marketing in a more rational dimension, which is considered the most appropriate approach to satisfy and retain customers. Thus, this article aims to analyze the effectiveness of Relationship Marketing - MDR in businesses, conducting a narrative, descriptive and exploratory bibliographic research of a qualitative nature. MDR in companies is a strategy focused on building and maintaining long-lasting relationships with customers, aiming not only at attracting them, but also at loyalty and ongoing satisfaction. This approach seeks to understand the needs and preferences of consumers, offering personalized experiences and quality service, which strengthens trust and loyalty to the brand. With the use of technologies and data, companies can monitor customer behavior and interact more efficiently, creating an emotional bond that goes beyond the simple commercial transaction. Therefore, we conclude with a complete analysis of MDR in this article, which we can say that it is clear that RM, if used appropriately, can lead to significant potential benefits in businesses.